2008
DOI: 10.1074/jbc.m801282200
|View full text |Cite
|
Sign up to set email alerts
|

How Protein Recognizes Ladder-like Polycyclic Ethers

Abstract: Ciguatoxins are a family of marine toxins composed of transfused polycyclic ethers. It has not yet been clarified at the atomic level on the pathogenic mechanism of these toxins or the interaction between a polycyclic ether compounds and a protein.Using the crystal structures of anti-ciguatoxin antibody 10C9 Fab in ligand-free form and in complexes with ABCD-ring (CTX3C-ABCD) and ABCDE-ring (CTX3C-ABCDE) fragments of the antigen CTX3C at resolutions of 2.6, 2.4, and 2.3 Å , respectively, we elucidated the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In a CIEA study, three carefully selected rFabs displayed K D values for free ABCD in the range of 2.4 × 10 −5 M to 5.0 × 10 −5 M. Moreover, rFab 1C49, exhibiting the highest affinity for ABCD, was also found to react to CTX-3C, though to a lesser extent. These last experiments and other studies [211,214] confirmed the importance of using more than four-ring fragments as synthetic haptens in designing valuable hapten-carrier conjugates for the production of high affinity and specific MAbs to CTX congeners.…”
Section: Methodologies For Ctxs Determinationsupporting
confidence: 69%
See 2 more Smart Citations
“…In a CIEA study, three carefully selected rFabs displayed K D values for free ABCD in the range of 2.4 × 10 −5 M to 5.0 × 10 −5 M. Moreover, rFab 1C49, exhibiting the highest affinity for ABCD, was also found to react to CTX-3C, though to a lesser extent. These last experiments and other studies [211,214] confirmed the importance of using more than four-ring fragments as synthetic haptens in designing valuable hapten-carrier conjugates for the production of high affinity and specific MAbs to CTX congeners.…”
Section: Methodologies For Ctxs Determinationsupporting
confidence: 69%
“…Up to now, in spite of many attempts, there is no fully validated immunoassay screening that is commercially available for ciguateric fish, but promising results have been obtained by Hirama’s group in Japan [207214]. As a general rule, in the course of producing Abs specific to Ags in laboratory animals, several critical steps must be carefully evaluated and planned such as: (i) the preparation and analysis of the Ags; (ii) the selection of the animal species in order to raise either only PAbs (e.g., sheep or rabbit) or PAbs plus MAbs (e.g., Balb/c mice); (iii) the selection of the adjuvant (e.g., Freund’s adjuvant); (iv) the development of an immunization schedule ( i.e., determine the dose, volume, route, number and site of injection, and intervals between injections); and (v) the monitoring of the Ab response (e.g., ELISA format assays).…”
Section: Methodologies For Ctxs Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that mAb 10C9 recognizes the entire pentacyclic skeleton (ABCDE ring) of CTX3C, and that the surface area required for molecular recognition of 10C9 is consistent with the prediction of 400 Å 2 . Probable recognition of mAb 10C9 and the pentacyclic ring moiety (ABCDE ring) of CTX3C was confirmed by crystal structure analysis of 10C9 complexed with ABCDE ring 15 [65] .…”
Section: Generation Of Anti-ctx Mabsmentioning
confidence: 99%
“…6). 71,72) Antibody 10C9 Fab has an extraordinarily large and deep binding pocket at the center of the variable region, where CTX3C-ABCDE fragment binds longitudinally in the pocket via hydrogen bonds and van der Waals interactions. Upon antigen-antibody complexation, 10C9 Fab adjusts to the antigen fragment by means of rotational motion in the variable region, and furthermore its recognition requires molecular rearrangements over the entire antibody structure.…”
Section: Determination Of the Absolute Configuration Of Ciguatoxins Amentioning
confidence: 99%